Clinical and Pathological Features of a Newborn With Compound Heterozygous ANKS6 Variants. (June 2020) - Kulkarni, Sakil; Abro, Brooj; Duque Lasio, Maria Laura; Stoll, Janis; Grange, Dorothy K; He, Mai
We report a term female infant born to nonconsanguineous parents who presented with renal failure at birth, hypothyroidism, cholestasis, and progressive cardiac dysfunction. Multigene next-generation sequencing panels for cholestasis, cardiomyopathy, and cystic renal disease did not reveal a unifying diagnosis. Whole exome sequencing revealed compound heterozygous pathogenic variants in ANKS6 (Ankyrin Repeat and Sterile Alpha Motif Domain Containing 6), which encodes a protein that interacts with other proteins of the Inv compartment of cilium ( NEK8, NPHP2/INVS, and NPHP3 ). ANKS6 has been shown to be important for early renal development and cardiac looping in animal models. Autopsy revealed cystic renal dysplasia and cardiomyocyte hypertrophy, disarray, and focal necrosis. Liver histology revealed cholestasis and centrilobular necrosis, which was likely a result of progressive cardiac failure. This is the first report of compound heterozygous variants in ANKS6 leading to a nephronopthisis-related ciliopathy-like phenotype. We conclude that pathogenic variants in ANKS6 may present early in life with severe renal and cardiac failure, similar to subjects with variants in genes encoding other proteins in the Inv compartment of the cilium.